Pornography Use and Loneliness: A Bidirectional Recursive Model and Pilot Investigation. Issue 2 (17th February 2018) - Butler, Mark H.; Pereyra, Samuel A.; Draper, Thomas W.; Leonhardt, Nathan D.; Skinner, Kevin B.
ABSTRACT: Sexuality is presumptively and observably a powerful core element of the human pair-bond relationship. Technological advances of the last half-century have made media a dominant cultural and developmental presence, including scripting sexual relationship attitudes and behavior. Theoretically and empirically, we examine loneliness as it relates to pornography use in terms of pornography's relational scripting and its addictive potential. Empirically, we examine the associative nature between pornography use and loneliness using a measurement model and two structural equation models where pornography use and loneliness are regressed on each other, respectively. Survey data were collected from a sample of 1, 247 participants, who completed an online questionnaire containing questions on pornography use, the University of California–Los Angeles Loneliness Scale (UCLALS), and other demographic variables. Results from our analyses revealed significant and positive associations between pornography use and loneliness for all three models. Findings provide grounds for possible future bidirectional, recursive modeling of the relation between pornography use and loneliness.